The Impact of Social Media Marketing Activities on Consumer Satisfaction and Purchase Intentions Mediated by Social Identification and Perceived Value on Social Media by Dr. Marteen - Muhammad Wildan Yuha Asa Rudianto; Muchsin Muthohar (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2024)
The rise of technology and the digital era has made the internet a crucial part of life, transforming it into a powerful marketing tool, known as e-marketing. E marketing broadens market reach, strengthens consumer relationships, and enhances satisfaction. Companies use it to efficiently share product information and expand their reach. This study explores the relationships between social media marketing, social identification, perceived value, and satisfaction within Dr. Marteen's marketing strategies, aiming to provide insights into social media marketing’s impact and offer practical recommendations for improving fashion industry marketing strategies.